PENGARUH TASK COMPLEXITY, TIME BUDGET PRESSURE, LOCUS OF CONTROL, PADA KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Clanira Uyani, (2022)
Audit quality is an examination of financial statements carried out by detecting material misstatements in the financial statements. The auditor's inability to detect deviations that may occur is one of the audit risks known as one measure of audit quality is the auditor's ability to anticipate detection risk. The purpose of this study is to test and empirically prove the effect of task complexity, time budget pressure, locus of control, on audit quality with auditor ethics as the moderating variable. The population of this research is the auditors who are in the AKN V and VI units of BPK RI. The sample of this study consisted of 54 respondents and used purposive sampling method. Data analysis was performed using Structural Equation Modeling (SEM) with SmartPLS software version 3.0. The results obtained in this study conclude that task complexity and locus of control have a significant effect on audit quality. time budget pressure has no significant effect on audit quality. auditor ethics cannot moderate the effect of task complexity, time budget pressure, and locus of control on audit quality. Keywords: Audit Quality, Task Complexity, Time Budget Pressure, Locus OfControl, Auditor Ethics